A DIAGNOSIS OF INTEGRATION RESEARCH AND ACADEMIC WORK AT THE UNIVERSITY (Educological discourse, 2015)
An article deals with results of statement stage of an experiment connected with a problem of integration research and educational work in future teachers’ university training. The criteria of the integration have been worked out. They are motivational, research, cognitive and efficient. The information about different aspects of integration research and education has been received from students and teachers as the result of questionnaire, discussions, observation. Questions deal with students’ science, mechanisms of students’ encouragement, factors that attract and do not attract students who are carrying out the research work. A real state of integration research and educational work in different universities of Ukraine implementing training of pedagogical staff has been given. A problem of integration research and educational work in future teachers’ university training has been revealed.